Expression of adaptor protein Ruk/CIN85 isoforms in cell lines of various tissue origins and human melanoma - Mayevska, O.; Shuvayeva, H.; Igumentseva, N.; Havrylov, S.; Basaraba, O.; Bobak, Y.; Barska, M.; Volod’ko, N.; Baranska, J.; Buchman, V.; Drobot, L. (Experimental Oncology, 2006)
Aim: Development of monoclonal and polyclonal antibodies against recombinant GST-fused proteins including correspondingly N- and C-terminal parts of Ruk/CIN85 adaptor protein. Analysis of Ruk/CIN85 expression patterns in cell lines of various tissue origins and human melanoma. Methods: Recombinant GST-fused fragments of Ruk/CIN85 were expressed in bacterial system and affinity purified. Monoclonal antibodies against SH3A domain of Ruk/CIN85 were produced using hybridoma technique. The specificity of generated antibodies was examined by ELISA. Polyclonal antibodies against C-terminal coiled-coil region of Ruk/CIN85 were affinity purified from serum of immunized rabbit. Expression patterns of Ruk/CIN85 isoforms and their subcellular localization in cell lines of various tissue origins and human melanoma samples were analyzed by immunoblotting, immunoprecipitation and immunofluorescence microcopy. Results: Ruk/CIN85 is ubiquitously expressed SH3-containing adaptor/scaffold protein which plays important roles in signalling processes. N-terminal half of Ruk/CIN85 molecule, including three SH3 domains, and its C-terminal coiled-coil region were used as antigens to produce monoclonal and polyclonal antibodies, respectively. Hybridoma cell lines secreting monoclonal antibodies (mAbs) to SH3 fragment of Ruk/CIN85 were established. One of the mAbs was extensively characterized and designated as MISh-A1. It was shown that this mAb recognizes an epitope, which resides within first SH3A domain. Polyclonal anti-Ruks Abs affinity purified from serum of immunized rabbit specifically recognized main Ruk/CIN85 isoforms, both endogenous and recombinant, in lysates of HEK293 cells. Notably, produced Abs did not cross-react with CD2AP, the member of the same family of adaptor/scaffold proteins. Multiple molecular forms of Ruk/CIN85 with apparent molecular weights of 130, 80–85, 70–75, 50–56, 34–40 and 29 kD were detected in cell lyzates of NIH3T3, Cos1, L1210, HEK293, Ramos, HeLa S3, MDCK, C6, A549 and U937 using anti-Ruk antibodies. Oligomerization between p85 and p50–56 forms of Ruk/CIN85 was revealed in C6 and NIH3T3 cells, but not in HeLa S3 and HEK293 cells by immunoprecipitation using MISh-A1 antibody following anti-Ruk Western-blot analysis. Using immunofluorescent microscopy and anti-Ruk antibodies, endogenous Ruk-variates were found mostly in cytoplasm of C6, NIH3T3, HEK293 cells and at lower level — in nuclei. Conclusion: Patterns of Ruk/CIN85 molecular forms expression are cell-specific and determined by cellular context. Assembly of oligomeric complexes between p85 and p50–56 Ruk/CIN85 isoforms in C6 and NIH3T3 cells but not in HeLa S3 and HEK293 cells may reflect their specific biological roles in different cell lines. High level of full-length Rukl/CIN85 form expression was revealed in extracts of human melanoma samples. Abs described in this paper may prove useful in future studies of Ruk/CIN85 expression and function in normal and transformed cells.